Memahami Nilai-Nilai Pancasila Sila Keempat di Kelas 4 SDN Gili Barat Guna Membangun Karakter dan Kebangsaan - Danar Rizky Rananda; Dya Qurotul A’yun (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research examines more closely how to understand the values ​​of the Fourth Pancasila in the philosophy of elementary school (SD) education in grade 4 at SDN Gili Barat in order to shape character and nationality. This research aims to analyze the practice of the four values ​​of Pancasila in the context of basic education and their impact on the development of students' personality and national awareness through a case study at SDN Giri Barat grade 4. The research methods used include classroom observations, interviews with grade 4 homeroom teachers, as well as school policy documentation. . The research results found that SDN Gili Barat thoroughly implemented the values ​​of the Fourth Pancasila in the learning process and school activities. A deep understanding of these values ​​will create an environment that supports the development of student character, including honesty, justice, courage and a spirit of mutual cooperation. Apart from that, this implementation also actively contributes to instilling national awareness and teaching students to love and appreciate Indonesia's cultural diversity. This research provides valuable insight for educators, researchers and educational practitioners to better understand the role of the Fourth Pancasila values ​​in shaping the character and nationality of students at the elementary school level. The implications of these findings can be used as a basis for developing more effective and sustainable educational strategies at the basic education level.